The Impact of Financial Ratios on Indonesian Telecommunication Stocks in 2019-2023 - Ni'masari, Diva Aulia; Sari, Pinky Permata (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2024)
This research examines the relationship between the financial ratios ROE, CR, and DER with the stock price in the Indonesian telecommunication industry. Using data from 2019 through 2023 for selected telecommunication companies listed on IDX, the study applies descriptive statistics and regression analysis to see the impact of these ratios on the movement of stock prices. The findings also show that ROE has a positive significant influence on stock prices, while the Debt-to-Equity Ratio negatively affects the prices of stocks. On the contrary, the Current Ratio does not significantly affect stock prices. In this regard, investors-especially from the middle class-should give more emphasis to profitability and leverage ratios as key elements in investment decisions in telecommunication stocks.